2011
DOI: 10.1007/s00296-011-2230-2
|View full text |Cite
|
Sign up to set email alerts
|

Living with scleroderma: patients’ perspectives, a phenomenological study

Abstract: In this study, it is aimed to determine the daily life experiences of patients on the basis their own way of statement. Sixteen patients with scleroderma were enrolled to this qualitative study. Data were collected using both a demographic data form and a semi-structured interview form. Study was made on individual patient interview by face-to-face manner. Data were evaluated using Colaizzi's phenomenological data analysis method. Data analysis revealed four categories and nine topics. These categories were (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…In addition, in a study involving 63 patients from four European countries, 19 concepts were shared among SSc patients from the four countries which included among others impaired hand function, household activities, paid work, drugs, climate and coldness, support from others and experiences with healthcare institutions, non-pharmacological treatment, social security and benefits [12]. Moreover, it has recently been reported that SSc patients experience difficulties regarding emotional, physical and social aspects and that individual abilities to cope with the disease were much more improved among patients who have a sustained social support [14]. Interestingly, none of the published studies identified the patient–physician relationship as of strategic importance in the care of SSc patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a study involving 63 patients from four European countries, 19 concepts were shared among SSc patients from the four countries which included among others impaired hand function, household activities, paid work, drugs, climate and coldness, support from others and experiences with healthcare institutions, non-pharmacological treatment, social security and benefits [12]. Moreover, it has recently been reported that SSc patients experience difficulties regarding emotional, physical and social aspects and that individual abilities to cope with the disease were much more improved among patients who have a sustained social support [14]. Interestingly, none of the published studies identified the patient–physician relationship as of strategic importance in the care of SSc patients.…”
Section: Discussionmentioning
confidence: 99%
“…The themes we identified in this study share similarities with the experiences of patients with other connective tissue diseases that involve a number of common clinical features with SLE, including rheumatoid arthritis and systemic sclerosis. Patients with rheumatoid arthritis also experience physical restriction, difficulties in maintaining social relationships, constant anxiety about the future, and loss of independence (). In comparison, patients with SLE and systemic sclerosis typically experience more diverse disease manifestations, including arthritis, sicca symptoms, alopecia, and Raynaud's phenomenon, and this can further contribute to loss of physical, social, and emotional functioning.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review identified 12 peer‐reviewed qualitative studies, including 380 patients, on the perspectives of patients with SSc , which found that patients face persistent uncertainties that undermine their self‐image, daily functioning, and identity. However, there are still knowledge gaps in the areas of information needs, attitudes to medications, self‐management, and support.…”
Section: Introductionmentioning
confidence: 99%